Board roles among Malaysian listed firms: Is agency theory relevant? - Ishak, Zuaini (Universiti Utara Malaysia, 2011)
This exploratory study examines the experiences of board members regarding their roles, board meeting, influence of board on appointment of new director, influence of “major” shareholders on board decision, and protection of interest of minority shareholders.Based on theories of board roles that underlie the study, semi-structured interviews were carried out amongst directors of Malaysian Public Listed Companies to collect relevant data on control and service roles.Results indicate that agency theory alone is insufficient to explain complex issues of board roles. Rather, better understanding can be achieved with the integration of agency theory and wider theoretical perspectives (i.e. stewardship and resource dependency). Although there is a constrain in accessing the board, this should not hamper future studies on examining other issues that could affect board roles such as effectiveness of chairman, non-executive directors and board sub-committees. Studies on this nature are important as the board has important influence on decision making process.